PENDIDIKAN AGAMA ISLAM DALAM RANGKA PENANGGULANGAN RADIKALISASI - Arum Rohmiyati; Irma Deni; Eko Sawandi; Milana Abdillah Subarkah (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2023)
The phenomenon of religious radicalism has become a global threat of the 21st century, the phenomenon is the result of Islam as an alleged religion and is often associated with terrorist religions. Educational institutions are often "suspected" in creating a generation of terrorists because the content of Islamic Religious Education Studies is dogmatic, indoctrination, and related to the spirit of da'wah that confirms truth claims. However, the substance of instructional materials used in high school does not contain inclusive religious content so as to create exclusive and intolerant religious behavior among high school students. The purpose of this study; 1). Provide a foothold among students of theological and sociological thought and behavior in order to have an inclusive and tolerant religiosity 2). Disseminating and seeding inclusive and tolerant ideas and behaviors of religiosity as a form of resistance ideology (deradicalization). 3). Fill the void of Islamic Religious Education literature Study of a special model of inclusive diversity relevant to mainstream Islam in Indonesia. To counteract religious radicalism among students, Islamic Religious Education Studies teaching materials must contain religiously inclusive content that includes Islamic teachings as the religion of Rahmatan Lil Alamin, a religion of tolerance supported by Qur'anic arguments and hadith. By using this teaching material model, it is expected that high school students will have inclusive religious behaviors that are relevant to the character and mainstream of Indonesian Islam in order to prevent radicalism among high school students.